The Unified Theory of Acceptance and Use of Technology (UTAUT) Used on Mobile Application: Literature Review - Deni Surya Permana; Nur Sayidah; Sri Utami Adi (Green Publisher Indonesia, 2024)
This paper aims to perform a systematic review of articles that have used the unified theory of acceptance and use of technology (UTAUT) from 2019 to 2023. The results in this research are based on the literature analysis of 10 existing articles on the UTAUT model. This has been performed by collecting data including demographic details, methodological details, limitations, and significance of relationships between constructs from the available articles based on the UTAUT. The findings indicated that general-purpose systems and specialized business systems were examined in the majority of the articles using the UTAUT. The analysis also indicated that the cross-sectional approach, survey methods, and structural equation modeling analysis techniques were the most explored research methodologies whereas Smart PLS was found to be the largely used analysis tool. This is the continued research that examined the literature on the UTAUT for the past five years and provided the researchers with accumulative knowledge about the model.